Eclipse A Novel - Hirano, Keiichiro (Columbia University Press, 2024)
In the late fifteenth century, a young Dominican friar sets out on a journey from Paris to Florence in search of manuscripts of pre-Christian philosophy. Along the way, he encounters an ascetic alchemist in a small village. As the young man falls under the spell of the alchemist's quest for enlightenment, a series of disasters-culminating in a total solar eclipse-strikes the village, with profound consequences.Keiichiro Hirano's Eclipse was a meteoric literary sensation when it first appeared in 1998. Its author, still an undergraduate, was hailed as a prodigy; the book received Japan's most prestigious literary award, the Akutagawa Prize, and became a bestseller. Set on the eve of the Renaissance in Europe, Eclipse depicts a society that is on the surface vastly different from modern-day Japan. Yet its account of a challenge to dualistic binaries and ossified worldviews holds striking contemporary resonance and philosophical depth. Taking the form of a memoir, Eclipse brings together an evocative portrayal of its historical setting, including the lore of medieval alchemy, with a rich literary lexicon, lush imagery, and psychological intricacy. This vivid translation offers Anglophone readers a vital work by one of Japan's most distinctive voices
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jan 2025)
Keywords: LITERARY CRITICISM / General